THE RELATIONSHIP AMONG ACCUMULATION RATE, STABLE ISOTOPE RATIO AND SURFACE TEMPERATURE ON THE PLATEAU OF EAST DRONNING MAUD LAND, ANTARCTICA - サトウ, カズヒデ; ワタナベ, オキツグ; ショウジ, ヒトシ; モトヤマ, ヒデアキ; SATOW, Kazuhide; WATANABE, Okitsugu; SHOJI, Hitoshi; MOTOYAMA, Hideaki (National Institute of Polar Research, 1999)
P(論文) During traverses in East Dronning Maud Land, which includes Dome Fuji Station (77°19′01″S, 39°42′12″E, elevation 3810m a.s.l.), many glaciological observations have been conducted by the Japanese Antarctic Research Expedition. Among the quantities observed are annual net accumulation (A_<cc> : kg m^<-2>), stable oxygen isotope composition (δ^<18>O : ‰) in the surface snow and mean annual surface temperature distribution. The characteristics of these quantities have been analyzed, and the following equation relating them was obtained : A_<cc>=1.104×10^5exp (0.1462δ^<18>O). In addition, a relation between δ^<18>O and surface temperature has been obtained. These relations suggest a possibility that core chronology and surface temperature variations can be reproduced from the δ^<18>O values in the 2500m-deep ice core drilled at Dome Fuji Station. departmental bulletin paper